Expression of calcitonin gene-related peptide and pulp sensitivity tests in irreversible pulpitis - Brenda Eréndida CASTILLO-SILVA; Verónica MARTÍNEZ-JIMÉNEZ; Gabriel Alejandro MARTÍNEZ- CASTAÑÓN; Carlo Eduardo MEDINA-SOLÍS; Eva Concepción AGUIRRE-LÓPEZ; Jesús Ramón CASTILLO-HERNÁNDEZ; Nereyda NIÑO-MARTÍNEZ; Nuria PATIÑO-MARÍN
Abstract The aim of the present study was to identify the relationship between the expression of calcitonin gene-related peptide (CGRP) and the responses of pulp sensitivity tests in healthy pulps and irreversible pulps by performing a cross-sectional study on patients. Two hundred subjects were evaluated. A total of 75 subjects complied with the criteria. The participants were divided into two groups: a) Healthy pulp (subjects [n = 35] having posterior teeth with clinically normal pulp tissue), and b) Irreversible pulpitis (subjects [n = 40] having posterior teeth with irreversible pulpitis). All participants were evaluated using the following variables: a) medical and dental history, b) pulp sensitivity tests, c) expression of CGRP by the enzyme-linked immunosorbent assay (ELISA), and d) expression levels of mRNA CGRP and mRNA CGRP receptor genes. We determined that the responses of the cold test between 4 and ≥12 s presented a higher average of the expression of CGRP in the group having irreversible pulpitis (p = 0.0001). When we compared the groups with the value of the electrical impulse, we found statistically significant differences (p = 0.0001), observing positive responses to the test with electrical impulses of 7 to 10, with an average of 72.15 ng/mL of CGRP in the irreversible pulpitis group. High values of CGRP expression were observed in that group in the responses of pulp sensitivity.